2019
DOI: 10.1002/jcp.28346
|View full text |Cite
|
Sign up to set email alerts
|

SNX9 determines the surface levels of integrin β1 in vascular endothelial cells: Implication in poor prognosis of human colorectal cancers overexpressing SNX9

Abstract: Angiogenesis, the formation of new blood vessels, is involved in a variety of diseases including the tumor growth. In response to various angiogenic stimulations, a number of proteins on the surface of vascular endothelial cells are activated to coordinate cell proliferation, migration, and spreading processes to form new blood vessels. Plasma membrane localization of these angiogenic proteins, which include vascular endothelial growth factor receptors and integrins, are warranted by intracellular membrane tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Recently, sorting nexin 9 (SNX9) regulates invadopodia formation and cell invasion in breast cancer cells [26,27]. SNX9 protein is highly expressed in tumor and tumor-endothelial cells of human CRC tissues [28], suggesting that SNX9 may also function in cell invasion/migration in the epithelial cells of CRCs, in addition to its novel function in angiogenesis of the endothelial cells. Thus, we stained SNX9 in human CRC tissues, and the results showed that high SNX9 expression in CRC cells (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, sorting nexin 9 (SNX9) regulates invadopodia formation and cell invasion in breast cancer cells [26,27]. SNX9 protein is highly expressed in tumor and tumor-endothelial cells of human CRC tissues [28], suggesting that SNX9 may also function in cell invasion/migration in the epithelial cells of CRCs, in addition to its novel function in angiogenesis of the endothelial cells. Thus, we stained SNX9 in human CRC tissues, and the results showed that high SNX9 expression in CRC cells (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that VEGFA‐mediated angiogenesis is the leading factor for the progression of breast cancer, lung cancer, and glioblastoma, providing essential nutrients for increased growth and tumor progression 5,20‐22 . The expression of integrin β1 in endothelial cell is essential for angiogenesis 23 . VEGF can interact with integrin by VEGFR2 and activate the binding function of multiple integrins in both endothelial and tumor cells through the PI3K/AKT pathway 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the deregulation of SNX9 expression contributes to many human diseases, including Lowe syndrome ( Nandez et al, 2014 ), Chlamydia-induced infection ( Hansch et al, 2020 ), chronic inflammation ( Ish-Shalom et al, 2016 ), and cancer ( Bendris et al, 2016a , b ). As a scaffold, changes in SNX9 expression could result in internal competition for binding partners, disrupting cellular activities, such as cell metastasis and angiogenesis ( Bendris et al, 2016a , b ; Bendris and Schmid, 2017 ; Tanigawa and Maekawa, 2019 ). Of note, recent studies have uncovered the vital role played by SNX9 in the pathogenesis of renal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Sorting nexin 9 (SNX9) maps to human chromosome 6q25.3 and was first identified for its role in clathrin-mediated endocytosis ( Bendris and Schmid, 2017 ). As a multifunctional protein, SNX9 plays vital roles in diverse endocytic vesicle sorting activities, the regulation of actin polymerization, cell migration and invasion, and cell division ( Soulet et al, 2005 ; Shin et al, 2008 ; Yarar et al, 2008 ; Bendris et al, 2016a ; Tanigawa and Maekawa, 2019 ). However, the expression pattern and potential biological functions of SNX9 during ADPKD remain unclear.…”
Section: Introductionmentioning
confidence: 99%